Rumah Panggung in Kampung Naga, West Java, Indonesia and Minka Gassho Zukuri in Shirakawa-go, Japan: The Local Wisdom of Traditional Houses in Mitigating Earthquake - Yani, Ahmad; Widaningsih, Lilis; Rosita, Rosita (TAWARIKH, 2016)
ABSTRACT: The objectives of this research is to explore the geological conditions and tales about earthquake narrated by local people in Indonesia and Japan; and the local wisdoms contained in traditional houses in Kampung Naga, West Java, Indonesia and in Shirakawa-go, Japan in relation to seismic resistant. This research employed qualitative approach, an approach that tends to have a subjective perspective. Sources of data were obtained from literature review, interviews, and a FGD (Focus Group Discussion). The results showed that although the traditional houses in Kampung Naga, Indonesia and in Shirakawa-go, Japan have many differences, but both architectural models have in common purpose to reduce the damage to the building in case of earthquake. Building resilience in both traditional houses has similarities to the foundation and the materials used. âRumah Panggungâ in Kampung Naga and âMinka Gassho Zukuriâ in Shirakawa-go do not have a rigid structure for their foundations, floors, and buildings. In the event of an earthquake, the houses just shifted their positions following the horizontal force of the earthquake. The buildings will move freely and return to their original positions after the quake without causing any serious damage. Difference between the two are house in Kampung Naga only uses materials that are lightweight and thin, while house in Shirakawa-go uses thick roof to adjust to the local climatic conditions. The people in Kampung Naga and Shirakawa-go are considered successful in building seismic resistant houses. KEY WORDS: Rumah Panggung in Kampung Naga, local wisdom, Minka Gassho Zukuri in Shirakawa-go, mitigation earthquake, and local natural conditions. Â  Â  About the Authors: Dr. Ahmad Yani is a Senior Lecturer at the Department of Geography Education, Faculty of Social Studies Education UPI (Universitas Pendidikan Indonesia or Indonesia University of Education) in Bandung. Dr. Lilis Widaningsih and Rosita, M.A. are Research Scholars at the UPI Bandung, Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. Corresponding author is: ahmadyani@upi.eduÂ How to cite this article? Yani, Ahmad, Lilis Widaningsih & Rosita. (2016). âRumah Panggung in Kampung Naga, West Java, Indonesia and Minka Gassho Zukuri in Shirakawa-go, Japan: The Local Wisdom of Traditional Houses in Mitigating Earthquakeâ in TAWARIKH: International Journal for Historical Studies, Vol.7(2) April, pp.275-296. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980.Chronicle of the article: Accepted (February 28, 2016); Revised (March 30, 2016); and Published (April 28, 2016).